'Encounters' are murders : a documentation of the 'Naxalite' policy of the Andhra Pradesh Government (Issued by Civil Rights (Tarkunde) Committee : copies available from Booklinks Corp., 1977)
Comprises press reportage, personal narratives, and two interim reports of the Civil Rights (Tarkunde) Committee, set up by Jai Prakash Narain in his capacity of president of Citizens for Democracy, 1977.